Lumbar tattoo and labour analgesia: a case of surgical approach - Duque, Mélanie (2017)
Introduction: Pregnant women with lumbar tattoo presenting for labour analgesia are currently increasing in number. Many anaesthesiologists are hesitant in placing an epidural catheter over a lumbar tattoo based on a theory that tissue coring of fragments of tattoo pigment into the epidural, subdural or subarachnoid space, could lead to epidermoid tumours or arachnoiditis. For these reasons, it has been recommended to avoid the introduction of epidural needle directly through skin with tattoo pigments. Case Report: We describe a case where the placement of the epidural catheter was made after a surgical incision of the skin to obtain a puncture field free from ink pigment. Conclusion: Surgical approach to epidural catheter placement reduces the risk of the pigment-entrainment phenomenon from the skin to the epidural space.